Analysis of The Relation of Traditional Values Nujuh Likur Forwach Tanjung Agung Village with Pancasila Student Profile Values - Heryanto, Debi; Yusnia, Yusnia; Agusdianita, Neza; Fitriani, Devi; Armando, Dego (Proceeding International Conference on Religion, Science and Education, 2025)
The role of education is very important for the Indonesian nation, aiming to increase its potential and abilities, form a dignified and polite national character, and educate the nation’s life. Therefore, the problem of education is not only about learning ability, but also the formation of students’ Pancasila character. This study aims to analyze the relationship between the values of the Nujuh Likur Melemang tradition and the values of the Pancasila student profile. This study uses a qualitative descriptive method, data collection techniques using interviews, and documentation. The study involved community leaders and the head of the customary advisory committee from Tanjung Agung Village, Kaur Regency. The results of this study found that there was a relationship between the values of the Pancasila student profile and the Nujuh Likur "melemang" tradition, namely the values of divinity, caring and togetherness, and the values of mutual cooperation.